2020
DOI: 10.1055/a-1300-1319
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic plastic stent therapy for bile leaks following total vs subtotal cholecystectomy

Abstract: Background and study aims Plastic biliary stents are standard therapy for treatment of post-cholecystectomy bile leaks. An increasing proportion of patients now undergo subtotal cholecystectomy and are at perceived risk for high-grade bile leak. Data are limited regarding the optimal endoscopic therapy following subtotal cholecystectomy. The aim of this study was to compare outcomes of endoscopic plastic stent therapy for treatment of bile leak following total vs subtotal cholecystectomy. Patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…ERCP can be applied not only in cases of biliary leakage but also for clearance of the biliary tract from residual stones, which can increase the common bile duct pressure and favour leakage from the cystic duct, especially if left open. These two complications were solved using ERCP in 95% of the population [53,54]. Early or late, this procedure can be applied for stenosis of the biliary tract post cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERCP can be applied not only in cases of biliary leakage but also for clearance of the biliary tract from residual stones, which can increase the common bile duct pressure and favour leakage from the cystic duct, especially if left open. These two complications were solved using ERCP in 95% of the population [53,54]. Early or late, this procedure can be applied for stenosis of the biliary tract post cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This complication is rarely fatal but requires correct treatment. If bile leakage does not stop spontaneously seven days postoperatively, the possible treatments are endoscopic biliary sphincterotomy [55], endoscopic plastic stent [54], and a fully covered self-expanding metal stent [54].…”
Section: Discussionmentioning
confidence: 99%
“…One of many possible complications of cholecystectomy is bile leakage, and in most studies it was reported to be more frequent during subtotal cholecystectomy (10). Stent placement for bile leak is a treatment option with high success rates (32). However, ERCP is associated to additional costs, time and the possibility of complications such as pancreatitis (3.5%), bleeding (1.3%) and/or perforation (0.6%) (22,33).…”
Section: Bile Leakagementioning
confidence: 99%
“…Therefore, EST alone is considered an option in minor leaks [6,7]. Biliary stenting using a plastic stent (PS) with or without EST is widely performed, with reported success rates of 53-100% [4,[8][9][10][11][12][13][14][15][16][17]; some cases are refractory and may require additional treatments including percutaneous or surgical interventions [17,18]. ENBD has several advantages such as reliable biliary decompression due cluding percutaneous or surgical interventions [17,18].…”
Section: Introductionmentioning
confidence: 99%